Decentralization and poverty reduction in Bolivia: Challenges and opportunities - Lykke Eg Andersen; Luis Carlos Jemio (Institute for Advanced Development Studies (INESAD), 2016)
This paper presents an analysis of the decentralization process that has been taking place in Bolivia over the last couple of decades. It starts with a review of the legal framework that determines the distribution of responsibilities and financial resources to the sub-national governments (9 departments and 339 municipalities), and continues with an analysis of the evolution and distribution of financing to these entities between 2001 and 2013. It then proceeds to describe the resulting progress in social indicators between 2001 and 2012 at the municipal level, and identifies the main remaining gaps in basic services by 2012. Finally, the paper offers an analysis of the factors that are most closely associated with progress in the main social indicator used by the Bolivian government - the Unsatisfied Basic Needs index. This provides the basis for a final section on recommendations for public investment in Bolivia.
Keywords: H70; H71; I38; O54; R11; R58; 330; Decentralization; poverty reduction; basic needs; Bolivia